Effect of Orthodontic Treatment on Anterior Tooth Displacement in Patients with Periodontal Disease: A Meta-Analysis - Jia Hou (Hindawi Limited, 2021)
Objective. To systematically evaluate the effect of orthodontic treatment (ODT) on anterior tooth displacement (ATD) in patients with periodontal disease. Methods. PubMed, Web of Science, Embase, China National Knowledge Infrastructure, and Wanfang databases were electronically searched for relevant literature studies on ODT and basic treatment for ATD in patients with periodontal disease, and then the related journals and reference lists of the included studies were manually searched. The search time was set from January 2010 to May 2021. Stata 16.0 software was used for meta-analysis. Results. Totally, 783 articles were retrieved, and finally, 14 studies were included. The effective rate of basic treatment combined with OTD was significantly higher than that of basic treatment alone (OR = 7.27, 95% CI: 3.76, 14.04). Specifically, the combined treatment led to lower values of periodontal pocket depth (SMD = −2.30, 95% CI: −2.94, −1.66), anterior overjet (SMD = −2.75, 95% CI: −3.72, −1.78), anterior overbite (SMD = −2.13, 95% CI: −3.16, −1.10), and periodontal bleeding index (SMD = −4.25, 95% CI: −5.48, −3.03) compared with those of basic treatment alone. Conclusion. Compared with basic treatment, ODT combined with basic treatment is more effective for patients with periodontal disease-caused ATD and can also improve the clinical symptoms of patients.